Feeding pattern of the African big barb Labeobarbus intermedius (Rüppel, 1836) (Pisces: Cyprinidae) in Ribb Reservoir, Lake Tana Sub-basin, Ethiopia - Agumassie Tesfahun; Sale Alebachew (Cogent Food & Agriculture)
The purpose of this study was to investigate the feeding patten of Labeobarbus intermedius at Ribb Reservoir (Lake Tana Sub-basin, Ethiopia). A total of 498 specimens were collected using gillnets. Of these, 302 (60.6%) fish had different foods, while 196 (39.4%) were empty. The fish were dissected, their stomachs were removed, and stomach contents were preserved in a 5% formalin solution. Frequency of occurrence, volumetric method, index of preponderance, and geometric importance index were used to study the feeding pattern. Detritus was the primary food, accounting for 61.6% of the guts by volume. Mud, zooplankton, and phytoplankton were the second most important food items comprising 24.4%, 3.9%, and 2.8% by volume respectively. Feeding pattern differed with the size classes of fish. The smallest fish (<16.5 cm Fork length) consumed detritus, mud, and insects comprised 64.2%, 18.7%, and 7.3% by volume, respectively. The adult fish (>17.0 cm FL) majorly consumed detritus followed by mud. The importance of mud increases when the fish grows more except (>31.5 cm FL) size class. The proportions of food items of L. intermedius significantly varied with respect to the dry and wet seasons. Detritus and mud were mostly consumed in the dry season, contributing to 47.8% and 32.4% by volume, respectively. Detritus was the most preferred food item during the wet season, contributing 97.2% of the total guts and 75.6% by volume. Generally, L. intermedius feeding pattern depending on size classes and seasonal variations this may be linked to food availability in the reservoir.